Rainfall homogeneous areas in Brazil - Filho, Thadeu Keller; Assad, Eduardo Delgado; Lima, Paulo Roberto Schubnell de Rezende (Pesquisa Agropecuaria Brasileira, 2005)
The objective of this work was to identify homogeneous areas in Brazil according to the similarity of their rainfall probability distribution, in order to contribute to the studies of climatic risks in agriculture. These areas were delimited using the hierarchical cluster analysis, with discriminating variables defined by the proportion of dry pentads and by measures of location, scale and shape of the pluviometric frequency distributions. Cluster analysis was able to identify 25 rainfall homogeneous areas in the whole Brazilian territory.